GRICE'S CONVERSATIONAL IMPLICATURE IN WRITTEN SHORT HUMOR DIALOGUES - Juliana, Nesya (2015)
The present study, entitled Grice's Conversational Implicature in Written Short Humor Dialogues examines the types of conversational implicature, hidden messages which are generated in written short humor dialogues, and audience's responses to implicatures. The present study uses 45 written short humor dialogues which are taken from www.squackle.com, www.lotsofjokes.com, www.englishindo.com, and www.jokes4u.com. The data were analyzed qualitatively by using Grice's conversational implicature (1975). The study is also supported by Hay's humor support strategies (2003) to analyze the audience's responses toward implicature. The study discovers that particularized conversational implicature is the only type of conversational implicature which appears in written short humor dialogues. Those particularized implicatures are generated through the failure in observing maxims, in the form of flouts. Moreover, flouts maxim of relation is the mostly flouted in the written short humor dialogues with 39 occurrences (86.7%) from 45 occurrences. With regard to audience's responses, they are obtained through a short interview with 20 students from English Education Department. The result of the interviews demonstrates that the audiences only use three strategies proposed by Hay (2003) which are 'contributing more humor' (53%), 'humor is support strategy itself' (22%), and 'mixed strategy' (1%) between 'contributing more humor' and 'offering sympathy'. All in all, the findings indicate that humors are easily made by flouting maxims. In addition, the audience's responses signify that the humor is funny and entertaining.----------Penelitian berjudul Grice's Conversational Implicature in Written Short Humor Dialogues membahas jenis-jenis implikatur percakapan yang muncul dalam dialog humor singkat, pembentukan pesan dalam dialog humor singkat, dan menganalisa respon dari audien terhadap implikatur dalam dialog humor singkat. Penelitian ini menggunakan data berupa 45 dialog humor singkat yang diambil dari www.squackle.com, www.lotsofjokes.com, www.englishindo.com, dan www.jokes4u.com. Data dianalisa dengan metode kualitatif menggunakan teori implikatur percakapan Grice (1975). Penelitian ini juga didukung oleh penggunaan teori strategi pendukung humor dari Hay (2003) untuk menganalisa respon dari audien terhadap implikatur. Dari penelitian ini ditemukan bahwa implikatur percakapan khusus merupakan satu-satunya jenis implikatur percakapan yang muncul dalam dialog humor singkat. Implikatur percakapan khusus dibentuk karena adanya pelanggaran terhadap maksim, yakni jenis flouts. Sebagai tambahan, flouts maxim of relation merupakan jenis maksim yang paling sering dilanggar dalam dialog humor singkat, dengan 39 kemunculan (86.7%) dari jumlah 45 humor dialog singkat. Mengacu terhadap respon responden terhadap implikatur diperoleh dengan melakukan wawancara singkat pada 20 orang siswa dari jurusan pendidikan bahasa Inggris. Hasil dari wawancara tersebut menunjukkan bahwa responden hanya menggunakan tiga strategi pendukung humor berdasarkan teori dari Hay (2003), yaitu contributing more humor (53%), humor is support strategy itself (22%), dan mixed strategy (1%) gabungan strategi contributing more humor and offering sympathy. Penemuan-penemuan di atas mengindikasikan bahwa humor dapat dengan mudah dibentuk melalui flouting maxims. Jawaban dari audien menandakan bahwa dialog humor singkat dianggap lucu dan menghibur.